2021
DOI: 10.3390/gels7040230
|View full text |Cite
|
Sign up to set email alerts
|

Development, Characterization, and Evaluation of α-Mangostin-Loaded Polymeric Nanoparticle Gel for Topical Therapy in Skin Cancer

Abstract: The aim of this study was to prepare and evaluate α-mangostin-loaded polymeric nanoparticle gel (α-MNG-PLGA) formulation to enhance α-mangostin delivery in an epidermal carcinoma. The poly (D, L-lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) were developed using the emulsion–diffusion–evaporation technique with a 3-level 3-factor Box–Behnken design. The NPs were characterized and evaluated for particle size distribution, zeta potential (mV), drug release, and skin permeation. The formulated PLGA NPs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 69 publications
1
29
0
Order By: Relevance
“…The functionalized nanodrug carrier system provides appropriate drug concentrations in the target after successful cell uptake, and internalization is mediated via endosomal escape and lysosomal fusion in the cytoplasm . The kinetic release results suggested that the simultaneous release of Dox and Gefit was caused by swelling of the polymeric matrix, dissolution, and water migration into polymeric NPs …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The functionalized nanodrug carrier system provides appropriate drug concentrations in the target after successful cell uptake, and internalization is mediated via endosomal escape and lysosomal fusion in the cytoplasm . The kinetic release results suggested that the simultaneous release of Dox and Gefit was caused by swelling of the polymeric matrix, dissolution, and water migration into polymeric NPs …”
Section: Discussionsupporting
confidence: 90%
“…65 The kinetic release results suggested that the simultaneous release of Dox and Gefit was caused by swelling of the polymeric matrix, dissolution, and water migration into polymeric NPs. 66 The hemolysis assay showed that the concentration of formulation tested for hemocompatibility was safe and compatible with the biological system. The study outcomes unveiled here are in agreement with a previous work.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The same quantity of gel was placed on a glass slide placed on top and left for 5 min before the spreading capacity was estimated. 32 5.2.13.5. Ex Vivo Permeation.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…They are capable of high drug loading, consecutively leading to an intensive transcutaneous drug flux. Despite their issues with short colloidal stability, PNP are widely studied as carriers for anti-inflammatory [ 29 ], anti-fungal [ 30 ], or immunosuppressive [ 31 ] actives. The last studied nanovesicles were ethosomes (ETZ) because of their extensive positive effects on the drug release to various layers of the skin.…”
Section: Introductionmentioning
confidence: 99%